Experimental investigation of glass fibre-reinforced polymer (GFRP) when subjected to low and high velocity impact events - Razali, Noorshazlin (2014)
The motivation for this work is to identify the high velocity impact damage in structures made from a composite material and to conduct an experimental study of a low velocity impact test by changes in the type of materials, number of layers and impact energy level using an IM10 Drop Weight Impact Tester. The composite material chosen for this research is Glass Fibre Reinforced Polymer (GFRP) in two forms: Type C-glass 600 g/m2 and Type E-glass 600 g/m2 . This material is fabricated using a heat blanket machine and vacuum bagging to produce laminated plate specimens of 100 mm × 100 mm with 6, 8, 10, and 12mm of thickness for high velocity impact testing. For low velocity impact test specimens, laminated plate specimens with a dimension of 100 mm × 150 mm were fabricated using a hand layup technique into 10 layers, 12 layers and 14 layers of GFRP woven roving plies. The high velocity impact test is performed on three specimens for each thickness using an instrumented Single Stage Gas Gun (SSGG) and the pressure of the gas gun is set to range from 5 bar to 60 bar. Each of the tests is performed using three types of bullet which are blunt, hemispherical and conical. The entire impact event capture from the impact test is recorded using the Ballistic Data Acquisition System. Meanwhile, the low velocity impact test is performed using an IM10 Drop Weight Impact Tester with a 10 mm hemispherical striker cap. The impact energy is set to 14, 28, 42 and 56 Joule with a velocity ranging from 1.73 m/s to 3.52 m/s for 10 layer specimens and 7, 14, 21, 28, 35, 42, 49 and 56 Joule for 12 layer and 14 layer specimens. The correlation between the impacted specimens and thicknesses is presented and discussed. A general trend was observed on the overall test which indicates that as the thickness or layers of the specimens and pressure increase, the energy absorbed also increases. The damage continues to increase as the velocity of the projectile increases. Impact damage was found to be in the form of fibre cracking, fibre breakage, matrix cracking and fibre pullout. Results from this research can be used as a reference in designing the structure of aircraft and body armour applications and in developing a better understanding of the test methods used to characterise impact behaviour.